Does yield loss due to weed competition differ between organic and conventional cropping systems?. (20th June 2016) - Benaragama, D; Shirtliffe, S J; Johnson, E N; Duddu, H S N; Syrovy, L D
Summary: High weed abundance in organic crops is thought to be a key factor contributing to the greater yield loss in organic as compared with conventional cropping systems. However, even with greater weed densities than conventional systems, some organic systems have yields comparable to conventional systems, suggesting that cropping systems might differ in yield loss due to weed competition. The diversity in soil nutrient resources due to diversity in crop rotations and variable inputs might enhance crop tolerance to weed competition. We assessed the long‐term effects of contrasting levels of crop rotations (low, medium and high diversity) on weed density, weed biomass and wheat yield loss in organic and no‐till conventional cropping systems using a microplot study within a long‐term cropping systems trial at Scott, Saskatchewan, Canada. Weed density and biomass were found to be four times higher in the organic systems than in the conventional systems. Under standard weed management practices, organic had 44% lower yield than the conventional system. Lower yields in organic, even without weed competition, suggest that the lower yields are due to low soil productivity rather than weed competition. No differences in yield loss were observed among the organic and conventional systems or among the diverse crop rotations. We conclude that the organic management practices and/or increased crop rotation diversity did not enhance yield or reduce yield loss due to weed competition, due to the factors associated with lower soil fertility.